2015
DOI: 10.3892/or.2015.4394
|View full text |Cite
|
Sign up to set email alerts
|

The natural compound codonolactone attenuates TGF-β1-mediated epithelial-to-mesenchymal transition and motility of breast cancer cells

Abstract: Codonolactone (CLT), a natural product, is the major bioactive component of Atractylodes lancea, and also found in a range of other medical herbs, such as Codonopsis pilosula, Chloranthus henryi Hemsl and Atractylodes macrocephala Koidz. This sesquiterpene lactone has been demonstrated to exhibit a range of activities, including anti-allergic activity, anti-inflammatory, anticancer, gastroprotective and neuroprotective activity. Previously, we found that CLT showed significant anti-metastatic properties in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 42 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…Codonolactone is the main bioactive component of Rhizoma Atractylodis macrocephalae . Both in vitro and in vivo studies have reported that codonolactone inhibited EMT and breast cancer metastasis by downregulating TGF‐β signaling pathway and Runx2 phosphorylation . Our experiment results confirmed that FH could prevent tumor metastasis in TNBC xenograft tumor zebrafish and reverse EMT in TGFβ1‐treated MDA‐MB‐231 cells.…”
Section: Discussionsupporting
confidence: 79%
“…Codonolactone is the main bioactive component of Rhizoma Atractylodis macrocephalae . Both in vitro and in vivo studies have reported that codonolactone inhibited EMT and breast cancer metastasis by downregulating TGF‐β signaling pathway and Runx2 phosphorylation . Our experiment results confirmed that FH could prevent tumor metastasis in TNBC xenograft tumor zebrafish and reverse EMT in TGFβ1‐treated MDA‐MB‐231 cells.…”
Section: Discussionsupporting
confidence: 79%
“…Antrocin exhibited inhibitory activity on the growth, migration, and invasion of human bladder cancer cells 30. Codonolactone also attenuated transforming growth factor-β1-mediated EMT and motility of breast cancer cells 31. Moreover, it has been reported that costunolide, derived from Saussurea lappa , induces apoptosis and inhibits cell migration and invasion in neuroblastoma cells 32.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, some compounds enriched from herbs or other natural sources have proven effective in blocking TGFβ-induced EMT, which may explain their potency in reducing the metastatic potential of breast cancer cell models in recipient mice [ 217 ]. One such compound is curcumin, which has been used in the treatment of various tumors and recently was shown to promote epithelial features in thyroid carcinoma cells by counteracting the actions of TGFβ.…”
Section: Development Of Drugs That Block Tgfβ-induced Emtmentioning
confidence: 99%